Muktātmyāpāsūna pramadvareparyanta - Vāḷimbe, Rā. Śã. (Rāmacandra Śaṅkara), 1911- (SAMP early 20th-century Indian books project ;, 1947)
Study of works of Gajanan Tryambak Madkholkar, 1899-1976, Marathi author.